Findings of a research trip by Paul Henze and Dorothea McEwan to rural churches in Tǝgray in 2025 textual descriptions and photographic records of 23 churches and monasteries - McEwan, Dorothea 1941- (2024)
The article presents a snapshot of the collections in ecclesiastical locations in Tigray. The many churches, which opened their eqa bet to P. Henze and the author, shared their pride in their objects in their stewardship - and also much more: their hope that urgent repair work on a number of objects should be done and could be done in the not too distant future. We listened to stories of the priests on local customs and history, we were able to see the church buildings and eqa bet and photographed a great amount of the precious objects in them. The rural churches in Tégray merit closer examination and assistance - which was the reason why we travelled with ato Kebede Amare Bälay, Chairman of the Tégray Culture and Tourism Commission. However, personal circumstances delayed the writing and publication of this report. The topic and the research findings are still a work in progress. It is therefore hoped that this article may contribute to greater understanding of what needs to be done to preserve and conserve the unique and unparalleled matchless collections of works of art in the local eqa bet. They represent the memory and cultural history of an important part of Ethiopian culture.
Farbige Illustrationen im Text
ohne Seitenzählung nach Seite 66: 22 farbige Illustrationen nach Seite 66
Keywords: Reisebericht -- 2005